Evaluating Fine Arts Learning Media: A Formative-Summative Evaluation Model In The Psychomotor Domain - Annida Zulfa; Rini, Sulistyo; Wicjaksono, Eko Bayu Putra; Ernawati; Razimmi, Muhammad; Marcella, Yulianda (Universitas Veteran Bangun Nusantara, 2025)
The evaluation of learning media in fine arts education is essential to ensure the achievement of students’ psychomotor learning outcomes, particularly at the elementary school level. However, systematic evaluation models that focus on skill-based learning remain limited in classroom practice. This study aims to examine and guide the evaluation of fine arts learning media for fourth-grade elementary school students using Scriven’s formative–summative evaluation model. A quantitative descriptive approach was employed to analyze the effectiveness of learning media in supporting students’ psychomotor development. Data were collected through observations, assessment instruments, and documentation of student performance, and were analyzed descriptively to capture learning progress and final outcomes. The results indicate that the formative–summative evaluation model consists of four key stages: needs assessment, program planning, formative evaluation, and summative evaluation. Formative evaluation provides continuous feedback during the learning process, while summative evaluation assesses students’ final performance and skill mastery. The findings demonstrate that this model enables teachers to systematically assess both learning processes and outcomes in fine arts instruction. This study contributes theoretically by strengthening the application of formative–summative evaluation in psychomotor learning and practically by offering a clear evaluation framework and assessment instruments that can assist teachers in improving fine arts learning media and student skill assessment.